2016
DOI: 10.1080/10618562.2016.1194402
|View full text |Cite
|
Sign up to set email alerts
|

Near-wall damping in model predictions of separated flows

Abstract: Data from the near-wall region of an attached and a separated turbulent boundary layer are used for the development of near-wall damping functions utilized in turbulence modelling. The model considered is an explicit algebraic Reynolds stress model. The data are taken from two direct numerical simulations. The turbulent boundary layer equation is analyzed in order to extend the validity of existing wall damping functions to turbulent boundary layers under severe adverse pressure gradients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…None of the four has a systematic derivation. (SeeSkote & Wallin (2016) for a review of current wall-damping functions, and an attempt to generalise them into a single model applicable to decelerating and separated flows.) With pressure gradient, −u′v′ deviates from u τ 2…”
mentioning
confidence: 99%
“…None of the four has a systematic derivation. (SeeSkote & Wallin (2016) for a review of current wall-damping functions, and an attempt to generalise them into a single model applicable to decelerating and separated flows.) With pressure gradient, −u′v′ deviates from u τ 2…”
mentioning
confidence: 99%
“…Wall functions that use the pressure-gradient (or some non-dimensional representation of it) have been previously explored in the context of incompressible flows by (for e.g.) Skote & Wallin [70]. Eddy viscosity formulations that use a pressure-gradient parameter such as the one given by Duprat et al [26] and Nituch et al [56] have shown promising results in adverse pressure-gradient, separated flows.…”
Section: Formulationmentioning
confidence: 99%